Neolamarckines A and B, New Indole Alkaloids from Neolamarckia cadamba. - Qureshi, Ahmad Kaleem; Mukhtar, Mat Ropi; Hirasawa, Yusuke; Hosoya, Takahiro; Nugroho, Alfarius Eko; Morita, Hiroshi; Shirota, Osamu; Mohamad, Khalit; A. Hadi, A. Hamid; Litaudon, M.; Awang, Khalijah (Pharmaceutical Society of Japan, 2011)
Two new indole alkaloids, neolamarckines A and B (1, 2) were isolated from the leaves of Neolamarckia cadamba (Rubiaceae). Structural elucidation of 1 and 2 was performed by combination of 2D-NMR and circular dichroism (CD) spectra, and chemical correlations. Neolamarckine A (1) showed inhibition of inducible nitric oxide synthase (iNOS) dose dependently.